Histological characterization of retinal degeneration in mucopolysaccharidosis type IIIC. (April 2023) - Ludwig, Jessica; Sawant, Onkar B.; Wood, Jill; Singamsetty, Srikanth; Pan, Xuefang; Bonilha, Vera L.; Rao, Sujata; Pshezhetsky, Alexey V.
Abstract: Heparan-α-glucosaminide N-acetyltransferase (HGSNAT) participates in lysosomal degradation of heparan sulfate. Mutations in the gene encoding this enzyme cause mucopolysaccharidosis IIIC (MPS IIIC) or Sanfilippo syndrome type C. MPS IIIC patients exhibit progressive neurodegeneration, leading to dementia and death in early adulthood. Currently there is no approved treatment for MPS IIIC. Incidences of non-syndromic retinitis pigmentosa and early signs of night blindness are reported in some MPS IIIC patients, however the majority of ocular phenotypes are not well characterized. The goal of this study was to investigate retinal degeneration phenotype in the Hgsnat knockout mouse model of MPS IIIC and a cadaveric human MPS IIIC eye. Cone and rod photoreceptors in the eyes of homozygous 6-month-old Hgsnat knockout mice and their wild-type counterparts were analyzed using cone arrestin, S-opsin, M-opsin and rhodopsin antibodies. Histological observation was performed on the eye from a 35-year-old MPS IIIC donor. We observed a nearly 50% reduction in the rod photoreceptors density in the Hgsnat knockout mice compared to the littermate wild-type controls. Cone photoreceptor density was unaltered at this age. Severe retinal degeneration was also observed in the MPS IIIC donor eye. To our knowledge, this is the first report characterizing ocular phenotypes arising from deleterious variants in the Hgsnat gene associated with MPS IIIC clinical phenotype. Our findings indicate retinal manifestations may be present even before behavioral manifestations. Thus, we speculate that ophthalmological evaluations could be used as diagnostic indicators of early disease, progression, and end-point evaluation for future MPS IIIC therapies.